Semi-quantitative study of macrobenthic fauna in the region of the South Shetland Islands and the Antarctic Peninsula - Arnaud, Patrick; López, Carlos; Olaso-Toca, Luis Ignacio; Ramil, Francisco; Ramos-Esplá, A.A.; Ramos, Ana (Polar Biology, 1998)
During the BENTART 95 Expedition, 24 Agassiz trawls for macrozoobenthos sampling were carried out at depths of 40–850 m, from north of Livingston Island to the Antarctic Peninsula. The samples were analysed using a semi-quantitative method, and with the resulting numerical data, transformed into a six-point scale, we constructed a Bray-Curtis similarity matrix. A total of 74,624 specimens, belonging to 38 taxonomic groups, were collected. The most abundant group was Polychaeta Sedentaria, with 36% of the total, whereas the highest relative masses were from Ascidiacea (23%), Echinoidea Regularia (18%) and Ophiuroidea (16%). The maximum number of specimens recorded was 15,600 ind./50 l. Cluster analysis separated stations located in Foster Bay (Deception Island), characterised by low taxonomic richness and high relative mass (average: 26.7 kg). A zonation of ascidians, regular sea urchins and ophiuroids was observed at Deception Island, clearly related to depth and substratum type. The remaining stations were separated into two groups. The first one comprised the shallowest stations (40–130 m), dominated by sessile active filter-feeders, belonging to Ascidiacea, Demospongia and Bryozoa, and probably related to high primary production zones. The second group comprised deeper stations and was dominated by classes exhibiting a diversity of trophic strategies: Ophiuroidea and Asteroidea, to 400 m, and Polychaeta Sedentaria at greater depths. SI